High sural nerve trifurcation: a rare anatomical variation - Tan, Eng Kee; Alias, Azammuddin; Yeak, Raymond; Jaafar, Mohd Shahril; M. Nizlan, Nasir (Springer Nature journal, 2022)
The sural nerve is a commonly encountered anatomical structure in foot and ankle surgeries. Knowledge of its location and course is imperative in performing surgeries within its vicinity to avoid neurological deficits. We herein report a rare anatomical variation of the sural nerve where it trifurcates above the level of the lateral malleolus that was discovered in a patient who underwent internal fixation for a trimalleolar ankle fracture with ipsilateral navicular fracture. This study aimed to raise awareness on a unique anatomical variation of the sural nerve in order to reduce the risk of iatrogenic injury.